2009
DOI: 10.1108/03068290910963716
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disability on the needs of caregivers

Abstract: Purpose-The perception among carers and health professionals is that the health care system remains limited in its effectiveness and accessibility to non-institutionalized people with a mental illness. The objective of this study is to determine the effect of the care recipient's main disabling condition (either physical or mental) on the carer's perceived need for assistance in their role as carer. Design-Based on the data collected from the Australian Survey of Disability, Ageing and Carers, the investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…The current study also found that carers with service demand for respite care had much greater overall need for support (85%) than their counterparts without service demand (38%), across multiple domains including respite care as well as financial, practical, and emotional or health support. Although not specific to respite care, previous research has shown that carers of persons with a psychological disability are 2.7 times more likely to report unmet care needs than carers of those with a physical disability 56 . Taken together, these findings suggest that the ‘packaging’ of services to meet the various needs of these carers through one channel may be beneficial 56 …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The current study also found that carers with service demand for respite care had much greater overall need for support (85%) than their counterparts without service demand (38%), across multiple domains including respite care as well as financial, practical, and emotional or health support. Although not specific to respite care, previous research has shown that carers of persons with a psychological disability are 2.7 times more likely to report unmet care needs than carers of those with a physical disability 56 . Taken together, these findings suggest that the ‘packaging’ of services to meet the various needs of these carers through one channel may be beneficial 56 …”
Section: Discussionmentioning
confidence: 86%
“…Although not specific to respite care, previous research has shown that carers of persons with a psychological disability are 2.7 times more likely to report unmet care needs than carers of those with a physical disability 56 . Taken together, these findings suggest that the ‘packaging’ of services to meet the various needs of these carers through one channel may be beneficial 56 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The perception of inadequate service assistance and unmet care needs of informal caregivers is greater among those caring for relatives with mental disabilities compared to those caring for relatives with physical disabilities (Vecchio et al, 2009(Vecchio et al, , 2008. Individuals with a mental disability require a different set of services to allow them to participate in the community and conduct their activities of daily living (Williams and Doessel, 2001).…”
Section: Discussionmentioning
confidence: 98%